Analysis of Compensation System Based on Job Value of Indonesian Cooks in Kuala Lumpur - Afrisca Azumanul Hakim; Lindawati Kartika; Zuraina Dato’ Mansor (AFEBI Management and Business Review, 2017)
Indonesian cooks is a kind of job that has a great potential to be developed, considering the high enthusiasm for Indonesian dishes in Malaysia and the popularity of Indonesian food in the world. This research aims to analyze the condition of compensation system currently applied to Indonesian Migrant Workers at cooks job cluster in Kuala Lumpur, as well as to identify the compensable factors, and to analyze the ideal compensation system. Data used in this research are primary data (questionnaire) and secondary data (literature study). This research used descriptive analysis, salary mapping analysis, point system method, and linear regression test in order to process the data. Result of the research shows (1) The evaluation result of Indonesian Migrant Cooks’ salary distribution has not been ideal entirely; (2) Compensable factors that used are knowledge and skill, organizational capabilities, self reliance, self presentation, responsibility of supervising, responses to critics, and the influence of work result; (3) The ideal compensation system for Indonesian Migrant Cooks in KL is non classification system based on Hay Plan Method, which the required funding is more efficient with amount RM 4,036.99 or about Rp.12,918,368.00.Keywords: Compensation System, Indonesian migrant workers